Morphological and molecular identifications of three native arbuscular mycorrhizal fungi isolated from the rhizosphere of Elaeis guineensis and Jatropha curcas in Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rini MV, Yelli F, Tambunan DL, Damayanti I. 2021. Morphological and molecular identifications of three native arbuscular mycorrhizal fungi isolated from the rhizosphere of Elaeis guineensis and Jatropha curcas in Indonesia. Biodiversitas 22: 4940-4947. Molecular analysis has been widely used to provide more accurate identification within arbuscular mycorrhizal fungi (AMF) species than identification based on morphology. However, morphological analysis is essential for a basic preliminary of classification studies. Therefore, a study is needed to complete the identification of AMF isolates through morphological and molecular analyses. This research used three AMF isolates, namely MV 5, MV 17, and MV 18, which were isolated from Indonesian agricultural land. Spore-based taxonomy (shape, size, color, ornamentation, PVLG, and Melzer’s reaction) and fungal colonization on roots of maize trap plants were employed for the morphological studies. AMF species identification was performed using molecular analysis through nested-Polymerase Chain Reaction (PCR) to amplify a fragment of SSU rRNA followed by sequencing and phylogenetic tree construction. Morphological analysis showed that MV 5 had spores borne from the neck of the sporiferous saccule, MV 17 was found to have a bulbous suspensor without a germination shield, and MV 18 had spores borne from subtending hyphae. The SSUR rRNA analysis revealed that MV 5, MV 15, and MV 18 were identified as Acaulospora longula, Gigaspora margarita, and Glomus etunicatum, respectively. Both morphological and molecular methods demonstrated reliable and consistent results that complement AMF taxonomy studies.
Keywords: arbuscular mycorrhizal fungi; AMF structure; molecular; morphology